How Do EFL Supervisors and Students Perceive the Journey of Thesis Writing? - Islami, Azzahra Nanda; Amrullah; Eryansyah (Universitas Hamzanwadi, 2024)
Thesis writing is a critical milestone for undergraduate students, yet it presents unique challenges for EFL learners who must navigate linguistic barriers alongside academic demands. In contexts where English is not the primary language, these challenges become even more pronounced, affecting both students’ writing competencies and the effectiveness of supervisory support. This study aimed to identify the primary challenges in thesis writing and supervision from the perspectives of undergraduate EFL students and their supervisors at a state university in South Sumatra, Indonesia. Additionally, it sought to uncover the reasons behind these difficulties and explore solutions proposed by supervisors to assist students in completing their undergraduate theses. Employing a descriptive qualitative design, the study involved 70 undergraduate students engaged in thesis writing and six lecturers serving as supervisors. Data were collected through questionnaires and interviews, with questionnaire data analyzed using percentage analysis and interview data subjected to thematic analysis. The findings revealed that students face challenges related to writing competencies and perceptions of supervisory support, including issues with topic selection, grammar, and effective communication. Supervisors identified seven key challenges and proposed actionable solutions, such as fostering consistent communication, encouraging extensive literature review, and improving adherence to institutional guidelines. These findings emphasize the need for a collaborative and structured approach to address the multifaceted challenges of thesis writing for EFL students.